45 - NURSING STAFF MAINTENANCE OF MECHANICAL VENTILATION CIRCUITS AND DEVICES IN THE PREVENTION OF INFECTION (Fiep Bulletin - online, 2011)
Introduction: the relative risk of mechanical ventilation-associated pneumonia (VAP) can be related to patient characteristics and the preventive care used by the health team, especially regarding circuits and devices used in this type of care. ObjectivE: to characterize the nursing team working in the ICU in a hospital in Natal/RN; to identify how the maintenance of circuits and devices used in Mechanical Ventilation patient assistance is being performed. Methodology: descriptive exploratory study, with quantitative approach and prospective data, performed between November 2007 and March 2008, with 25 nursing professionals. Results: we detected a young population, female mostly, nursing technicians and never having been through VAP prevention training; regarding the circuits and devices care: in 84.6% the daily aspirator vial replacing was not done; 50.05% of the observations the ambu was not replaced; on most occasions (65.2%), nebulization was inadequately manipulated; on 55.0% of the times the condensed matter formed in the MV circuits was discarded; on most observations (92.6%), water used for humidifying the air generated by the MV was sterile; on 78.4% of the observations, professionals did not fill up the humidifier, on 97.0% the MV circuits were replaced when there was dirtiness or defect. Conclusion: Many of the maintenance procedures were not correctly performed, so there is a considerable exposure of the patient to infections that may worsen the prognosis and increase hospitalization time.
Keywords: Mechanical Ventilation-Associated Pneumonia (VAP); Intensive Care Units; Nursing Care